1993
DOI: 10.2190/1w2e-mxyx-gugt-fypr
|View full text |Cite
|
Sign up to set email alerts
|

AIDS-Related Knowledge, Attitudes, Beliefs, and Behavioral Intentions of Adolescents in Trinidad: A Pilot Study

Abstract: Ninety-six percent of respondents knew the cause of AIDS and mode of transmission, but 26 percent felt that they could get AIDS from insect bites. Student knowledge did not correlate with behavior intentions, but there was a high correlation with perception of risk and their intention to use condom or abstain from sexual practice. There appears to be some association between level of education and likelihood of safe sexual practices (p = .06). There was a significant (p < .05) relationship between students att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…While information about the seriousness of HIV is not readily available for the adolescent population, adolescents are not usually worried that they may contract HIV [25,26,29]. Both groups in our study had high perceived susceptibility for contracting HIV, with the intervention group viewing themselves as more susceptible to the disease than the comparison group.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…While information about the seriousness of HIV is not readily available for the adolescent population, adolescents are not usually worried that they may contract HIV [25,26,29]. Both groups in our study had high perceived susceptibility for contracting HIV, with the intervention group viewing themselves as more susceptible to the disease than the comparison group.…”
Section: Discussionmentioning
confidence: 80%
“…Another study conducted among young people in Guyana between the ages of 12-20 years in which 95.6% of the respondents also knew that HIV can be transmitted by having sexual intercourse with someone who is HIV positive [25]. In two earlier studies conducted in Trinidad and Nigeria among secondary school students 100% and 83.3% of the respective secondary schools knew that AIDS was transmitted by sexual contact [26,27].…”
Section: Discussionmentioning
confidence: 97%
“…Many perceived low vulnerability to STIs and view their partners as trustworthy, which correspond to the perceived susceptibility construct of the HBM. Previous studies showed that adolescents’ perceived risks of STIs not only influence their intentions to use condoms, but are associated with abstaining from sexual intercourse [44]. The findings suggest that the design of communication messages to increase condom use should be guided by the perceived susceptibility construct of the HBM.…”
Section: Discussionmentioning
confidence: 84%